Plays As an Apparatus of Change: a Study of Play Family Saga: Examining the Role of Theatre in Transforming Oppressor and Oppressed (Journal of Advances and Scholarly Researches in Allied Education, 2013)
This  article argues  that  theatre as  an  apparatus of  change  has for  a long  time privileged  thetransformation  of  the oppressed  people  by inciting  their  conscience and  consciousness.  This incitement is meant to make them takeaction, leading to some kind of social and political agency. However, thisarticle argues that the oppressor equally needs to be changed. Therefore theatre/dramaas a tool of intervention should be framed in such a way that it providespossibilities for the oppressor to change instead of acting as an imaginarythat only privileges the vanquishing of the oppressor. Thearticle takes recourse in John OToolesexperiment with theatre in education process to advance its arguments in regard to Bole Butakes drama andspecifically his play „Family Saga.